Pharmacological inhibition of Bmi1 by PTC-209 impaired tumor growth in head neck squamous cell carcinoma - Wang, Qiong (Cancer Cell Int, 2017)
BACKGROUND: Bmi1 (B lymphoma Mo-MLV insertion region 1 homolog) contributes to human tumorigenesis via epigenetic transcriptional silencing and represents a novel therapeutic target with great potentials. Here we sought to determine the therapeutic efficiency of PTC-209, a potent and selective Bmi1 inhibitor, in head neck squamous cell carcinoma (HNSCC) cells and a HNSCC xenograft model. METHODS: The mutation pattern, mRNA level of Bmi1 in HNSCC and its associations with clinicopathological parameters were determined through comprehensive data mining and interrogation using publicly available databases GENT, cBioPortal, Oncomine and TCGA. The PTC-209, a selective and potent Bmi1 inhibitor, was exploited and its effect on Bmi1 expression was measured in two HNSCC cell lines Cal27 and FaDu. The phenotypical changes of HNSCC cells were observed upon PTC-209 treatment in vitro. Moreover, the therapeutic effects of PTC-209 for HNSCC were determined in a xenograft animal model. RESULTS: Through comprehensive data mining and interrogation, we found that Bmi1 mRNA was frequently overexpressed in a subset of HNSCC samples. Our data revealed that PTC-209 robustly reduced the expression of Bmi1 in Cal27 and FaDu cells presumably by post-transcriptional repression and ubiquitin-proteasomal degradation. PTC-209 treatment resulted in impaired cell proliferation, G1-phase cell cycle arrest, compromised migration and invasiveness, and increased cell apoptosis and chemosensitivity to 5-FU and cisplatin in vitro. Moreover, PTC-209 exposure reduced colony formation, tumorsphere formation and the percentage of ALDH1(+) subpopulation in both Cal27 and FaDu cells. Importantly, in vivo PTC-209 administration significantly reduced tumor growth in a HNSCC xenograft model probably by Bmi1 inhibition and impaired cell proliferation. CONCLUSIONS: Our findings indicate that pharmacological inhibition of Bmi1 is a novel therapeutic strategy for HNSCC patients, especially with those with aberrant Bmi1 overexpression. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12935-017-0481-z) contains supplementary material, which is available to authorized users.